Financial Literacy Enhancement for University Students in Kartasura, Central Java - Perwithosuci, Winny; Putri, Rania Nurdiana (Universitas Muhammadiyah Surakarta, 2025)
Financial literacy is one of the key areas of knowledge that enables people, including students, to manage their personal finances effectively. This individual-level skill can improve their finances through wise consumption, savings, and investment decisions. Students who live away from home and live in boarding houses, rent houses near campus, or live with other relatives often face challenges in managing their finances. A survey of student respondents living in boarding houses in Kartasura City, Central Java, showed that they face challenges in managing their finances. These challenges include difficulty in saving. 88% of respondents admitted to having difficulty saving due to excessive spending and an inability to prioritize needs over wants. In response to this phenomenon, this community service program aims to provide knowledge on managing personal finances and saving. Moreover, this activity also provides knowledge about investment products. It aims to help participants increase the real value of their money, thereby enabling them to achieve their financial goals more quickly. As a result, participants were motivated to be more disciplined in managing their finances. 80% of participants intended to add bank accounts to increase their savings. Furthermore, there was an increase in interest in investing through mutual funds and stocks. These results demonstrate the program’s success and serve as a topic for future community service activities.